Towards the systematic identification of low-cost ecosystem-mediated carbon sequestration opportunities in bioenergy supply chains - Field, John L., author; Willson, Bryan, advisor; Paustian, Keith, advisor; Bradley, Thomas, committee member; Leach, Jan, committee member; Marchese, Anthony, committee member (Colorado State University. Libraries, 2015)
Because the dedicated production of terrestrial biomass feedstocks involves the fixation of atmospheric carbon, carefully managed biofuel and bioenergy supply chains are increasingly recognized as an opportunity for carbon sequestration in soils or geological reservoirs in addition to their climate change mitigation value via the displacement of fossil fuel use. Bioenergy involves the coupling of agricultural systems and industrial supply chains, and finding optimal system designs often requires navigating a fundamental tension between maximizing overall system productivity while simultaneously limiting the intensification of feedstock exploitation to sustainable levels. Bioenergy sustainability analyses are further complicated by strong spatial heterogeneities in feedstock production performance, fundamentally different emission mechanisms across the agricultural and industrial phases of the biofuel lifecycle, and the tendency to perform environmental assessments and economic analyses in isolation. Well-designed integrated assessments are necessary to identify the total amounts and time dynamics of sequestration possible in such systems, to put those results in context relative to other supply chain impacts, and to understand tradeoffs between various environmental impact criteria and production costs. This dissertation starts with a thorough review of the bioenergy lifecycle assessment (LCA) literature to identify outstanding climate impact accounting challenges and inform the integration of production cost estimates. Two integrated assessment case studies are then undertaken to identify low-cost opportunities for improving carbon sequestration at different points in the bioenergy supply chain. The first focuses on feedstock production, assessing the potential for increasing soil carbon sequestration in bioenergy landscapes based on the cultivation of perennial grasses. A spatially-explicit landscape analysis system is created around a newly-parameterized version of the DayCent biogeochemistry model, and switchgrass productivity and soil greenhouse gas balance are assessed across gradients of land quality and cultivation intensity in a real-world bioenergy landscape in western Kansas. Integrating these ecosystem simulation results with existing LCA, farm enterprise budget, and biomass transport models allows for the quantification of landscape level cost – mitigation tradeoffs under various system design strategies and policy constraints. The second case study focuses downstream in the supply chain, considering the use of low-value conversion co-products as soil amendments to improve agroecosystem sustainability. The biochar co-product from a hypothetical thermochemical conversion system in the Colorado Front Range is assessed using simplified models of biochar recalcitrance and agronomic benefits as a function of feedstock material and conversion method. Together, these case study results are illustrative of the potential costs of improving ecosystem-mediated carbon sequestration in bioenergy systems, and the ongoing work required for full global supply chain optimization.
Keywords: bioenergy; biogeochemistry; biochar; lifecycle assessment; biofuels